2014
DOI: 10.1186/1532-429x-16-35
|View full text |Cite
|
Sign up to set email alerts
|

A novel and practical cardiovascular magnetic resonance method to quantify mitral annular excursion and recoil applied to hypertrophic cardiomyopathy

Abstract: BackgroundWe have developed a novel and practical cardiovascular magnetic resonance (CMR) technique to evaluate left ventricular (LV) mitral annular motion by tracking the atrioventricular junction (AVJ). To test AVJ motion analysis as a metric for LV function, we compared AVJ motion variables between patients with hypertrophic cardiomyopathy (HCM), a group with recognized systolic and diastolic dysfunction, and healthy volunteers.MethodsWe retrospectively evaluated 24 HCM patients with normal ejection fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 18 publications
(23 reference statements)
1
27
0
5
Order By: Relevance
“…This process produces a map of the correlation between the point (and its surroundings) in the initial image and the points within that corresponding neighborhood in the subsequent image; the location of the maximum correlation represents the likely location of the initial point (and its surrounding template) within the subsequent image. In this study, NCC enabled semi-automated AVJ tracking that reduced the long post-processing time previously required with manual AVJ tracking [19]. In addition, the use of reproducibility analyses here showed that the use of NCC limited variability in calculated MA sweep volume measurements between users.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This process produces a map of the correlation between the point (and its surroundings) in the initial image and the points within that corresponding neighborhood in the subsequent image; the location of the maximum correlation represents the likely location of the initial point (and its surrounding template) within the subsequent image. In this study, NCC enabled semi-automated AVJ tracking that reduced the long post-processing time previously required with manual AVJ tracking [19]. In addition, the use of reproducibility analyses here showed that the use of NCC limited variability in calculated MA sweep volume measurements between users.…”
Section: Discussionmentioning
confidence: 87%
“…The atrioventricular junction (AVJ), the septal and lateral junction between the left atrium and ventricle, was tracked in two-, three-, and four-chamber long-axis CMR views over the cardiac cycle [19]. This was performed semi-automatically in lab-written MATLAB (MathWorks Inc., MA, USA) using normalized cross-correlation (NCC), a well-known feature-tracking algorithm [23,24] that has been used in MA location tracking in CMR [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cardiovascular magnetic resonance imaging (MRI), methods exist that can measure those diastolic parameters (Paelinck et al 2005;Bollache et al 2010;Duarte and Fernandez 2010;Leng et al 2015;Saba et al 2014;Seemann et al 2017). For example, quantification of LA volumes is established (Wylie et al 2008;Maceira et al 2010), but there is a lack of standardized methods for MRI assessment of diastolic parameters linked to valvular flow and motion (i.e., E, A, and especially e 0 ).…”
Section: Introductionmentioning
confidence: 99%
“…The phenotyping of cardiomyopathy is a primary clinical indication for CMR, and has become mainstream in hypertrophic cardiomyopathy, [5759] including the development of hypertrophy atlases [60]. Recent attention has been focussed on T1 imaging for the assessment of diffuse fibrosis in cardiomyopathy, [61, 62] with T1 standardisation, [63] technical developments, and the assessment of diffuse fibrosis in cardiomyopathy.…”
Section: Cardiomyopathymentioning
confidence: 99%